2009
DOI: 10.1007/s11274-009-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of fungal ligninolytic enzymes by ultrafiltration and their use in distillery effluent decolorization

Abstract: Extracellular ligninolytic enzymes secreted by seven different fungi grown under solid-state fermentation using agro-residue as substrate were extracted through successive extractions. In general, most of the enzymes were recovered during first and second extractions. These extractants were then subjected to ultrafiltration using a 10 kDa membrane for further concentration. The permeates collected after every filtration and the final retentate were analyzed for protein and enzymes. In all the isolates, enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Previously, Soares et al [38] had also reported that increasing concentration of laccase increased the rate of dye decolorization. Similarly, Pant and Adholeya [39] reported that the concentrated laccase from P. florida EM1303 obtained by ultrafiltration efficiently decolorized undiluted distillery effluent. This further proves the P. florida laccase utility in treating various effluents.…”
Section: Resultsmentioning
confidence: 86%
“…Previously, Soares et al [38] had also reported that increasing concentration of laccase increased the rate of dye decolorization. Similarly, Pant and Adholeya [39] reported that the concentrated laccase from P. florida EM1303 obtained by ultrafiltration efficiently decolorized undiluted distillery effluent. This further proves the P. florida laccase utility in treating various effluents.…”
Section: Resultsmentioning
confidence: 86%
“…Hence, in recent years, the importance of biological wastewater treatment systems has attracted the attention of workers the world over and has helped in developing efficient low cost waste treatment systems. Increased attention has been directed towards utilization of microbial activity for the mineralization and decolorization of vinasse (Pant and Adholeya 2007a, b, c;Pant and Adholeya 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Especially TiO 2 , ZnO or their different modifications, such as metal-or alkaline-doped versions, have been used in photocatalytic processes as catalyst because of their huge capacity to produce higher amount of hydroxyl radicals [24][25][26]. On the other hand, some applications of biological wastewater treatment based on fungi have been used by researchers although satisfied results may not be reached [27].…”
Section: Introductionmentioning
confidence: 99%